The Macroeconomic Effects of Environmental Taxes : A Closer Look at the Feasibility of 'Win-Win' Outcomes - Ligthart, Jenny (IMF Working Papers; Working Paper, 1998)
This paper reviews recent literature on the macroeconomic effects of environmental taxes. It attempts to delineate the conditions under which a cleaner environment is compatible with attaining macroeconomic objectives, such as more employment and economic growth. The analysis reveals that an environmentally motivated fiscal reform-using the revenues from environmental taxes to cut labor taxes-may yield employment and environmental dividends if the tax burden can be shifted to agents outside the labor market, such as capitalists, transfer recipients, and foreigners. A cleaner environment and a higher rate of economic growth go hand in hand if the environment is considered an important public input into production.